Evaluation of Performance of Detection of Immunoglobulin G and Immunoglobulin M Antibody Against Spike Protein of SARS-CoV-2 by a Rapid Kit in a Real-Life Hospital Setting - Irungbam, Monica; Chitkara, Anubhuti; Singh, Vijay Kumar; Sonkar, Subash Chandra; Dubey, Abhisek; Bansal, Aastha; Shrivastava, Ritika; Goswami, Binita; Manchanda, Vikas; Saxena, Sonal; Saxena, Ritu; Garg, Sandeep; et al. (Frontiers in Microbiology, 2022)
Background Antibody testing is often used for serosurveillance of coronavirus disease 2019 (COVID-19). Enzyme-linked immunosorbent assay and chemiluminescence-based antibody tests are quite sensitive and specific for such serological testing. Rapid antibody tests against different antigens are developed and effectively used for this purpose. However, their diagnostic efficiency, especially in real-life hospital setting, needs to be evaluated. Thus, the present study was conducted in a dedicated COVID-19 hospital in New Delhi, India, to evaluate the diagnostic efficacy of a rapid antibody kit against the receptor-binding domain (RBD) of the spike protein of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Methods Sixty COVID-19 confirmed cases by reverse transcriptase–polymerase chain reaction (RT-PCR) were recruited and categorized as early, intermediate, and late cases based on the days passed after their first RT-PCR–positive test report, with 20 subjects in each category. Twenty samples from pre-COVID era and 20 RT-PCR–negative collected during the study period were taken as controls. immunoglobulin M (IgM) and immunoglobulin G (IgG) antibodies against the RBD of the spike (S) protein of SARS-CoV-2 virus were detected by rapid antibody test and compared with the total antibody against the nucleocapsid (N) antigen of SARS-CoV-2 by electrochemiluminescence-based immunoassay (ECLIA). Results The detection of IgM against the RBD of the spike protein by rapid kit was less sensitive and less specific for the diagnosis of SARS-CoV-2 infection. However, diagnostic efficacy of IgG by rapid kit was highly sensitive and specific when compared with the total antibody against N antigen measured by ECLIA. Conclusion It can be concluded that detection of IgM against the RBD of S protein by rapid kit is less effective, but IgG detection can be used as an effective diagnostic tool for SARS-CoV-2 infection in real-life hospital setting.